IN INDIA, THE RIGHT TO A FAIR TRIAL IS A CRUCIAL ELEMENT OF THE INDIAN LEGAL SYSTEM – AN ANALYSIS - G, Sudharsana Moorthy; Rao, B Someswara; Naidu, S. T. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Fair trial is a legal right that ensures that all individuals are treated equally under the law, irrespective of their race, gender, social status, or any other characteristics. A fair trial is a fundamental right that is enshrined in the constitutions of many democratic countries, and it is essential to protect the rights of individuals and ensure that justice is served. Fair trial is a cornerstone of any justice delivery system. In India, the right to a fair trial is an essential component of the Indian legal system. In Judicial proceedings, a fair trial is considered a fundamental human right of all individuals charged with any punishable offences. The fair trial has been recognized both at national and international levels.